Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
2d + 1/6 = 2d+ 6
0d = 6 - 1/6
This is not a valid solvable question
0d = 6 - 1/6
This is not a valid solvable question
2d+1/6= 6(1/3d +1)
=multiply
2d+1/6 =6/3d + 6
-1/6 -1/6
d*(2d) = (2/d + 5.8) *d
2d^2 = 7.8
/2 /2
√d^2 =√3.9
d =1.9
=multiply
2d+1/6 =6/3d + 6
-1/6 -1/6
d*(2d) = (2/d + 5.8) *d
2d^2 = 7.8
/2 /2
√d^2 =√3.9
d =1.9
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.